Nevoid trichorrhexis invaginata (bamboo hairs). - Selvaag, E.; Borup, M. (European Journal of Pediatric Dermatology, 2018)
We present a boy with breakage of hair on the vertex and along stripes across the scalp. Scanning electron microscopy of the hairs from these regions showed typical invaginations. In addition the boy suffered from atopic eczema. Trichorrhexis invaginata is usually found in patients with ichthyosis linearis circumflexa and allergie predisposition. This association of symptoms and signs is named Comel-Netherton’s syndrome. It is inherited by an autosomal recessive trait, with a higher penetrance in females. This case probably represents a spontaneous, postzygotic, somatic mutation, presenting in a nevoid pattern in a boy.